Dual Effect of Income Diversification and Digital Transformation on Banks' Profitability in Asian Countries - Thi Thuy Hang Le; Le Tuan Hiep (Ianna Journal of Interdisciplinary Studies)
Background: Income diversification and digital economic transformation are inevitable trends in banking activities today, in line with the development of technology and customer needs; further diversifying income increases a bank's financial efficiency and has the power to positively regulate other factors towards increasing profitability.